2022
DOI: 10.5223/pghn.2022.25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin and Phenotype Severity in Patients with Cystic Fibrosis: A Systematic Review and Meta-Analysis

Abstract: Inflammation plays an important role in the outcome of patients with cystic fibrosis (CF). It may develop due to cystic fibrosis transmembrane conductance regulator protein dysfunction, pancreatic insufficiency, or prolonged pulmonary infection. Fecal calprotectin (FC) has been used as a noninvasive method to detect inflammation. Therefore, the aim of the current meta-analysis was to investigate the relationship between FC and phenotype severity in patients with CF. In this study, searches were conducted in Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, fecal calprotectin levels have been found to correlate with markers of nutritional status and pancreatic function, suggesting a link between intestinal inflammation and malnutrition in cystic fibrosis. A meta-analysis by Talebi et al [ 142 ] found that median fecal calprotectin levels were inversely associated with body mass index (BMI) and BMI Z score, reflecting the nutritional status of the patients. However, Adriaanse et al [ 143 ] found this negative correlation in adult patients and not in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, fecal calprotectin levels have been found to correlate with markers of nutritional status and pancreatic function, suggesting a link between intestinal inflammation and malnutrition in cystic fibrosis. A meta-analysis by Talebi et al [ 142 ] found that median fecal calprotectin levels were inversely associated with body mass index (BMI) and BMI Z score, reflecting the nutritional status of the patients. However, Adriaanse et al [ 143 ] found this negative correlation in adult patients and not in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, Adriaanse et al [ 143 ] found this negative correlation in adult patients and not in children. Studies have shown that fecal calprotectin levels are higher in patients with cystic fibrosis and pancreatic insufficiency, indicating a potential association between pancreatic status and intestinal inflammation[ 27 , 142 ]. However, studies also observed increased fecal calprotectin in children with or without pancreatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gut inflammation seems to influence CF severity, including risk of lung infection and progressive deterioration. In a systematic review of studies regarding fecal calprotectin and phenotype severity in CF patients, Talebi et al reported that there were significant correlations between fecal calprotectin and the factors that characterize a more severe CF phenotype, including colonization by P. aeruginosa , predicted FEV1 <50%, pancreatic insufficiency, and underweight status [ 68 ]. Moreover, reduced gut microbiota diversity has been found associated with lower FEV1 values [ 23 ] and increased risk of pulmonary exacerbations [ 25 ].…”
Section: Impact Of Gut Dysbiosis In Cystic Fibrosis Patientsmentioning
confidence: 99%
“…A recent survey revealed a high rate of abdominal complaints with a likely origin in the lower gut in CF patients not suffering from recurrent DIOS episodes [ 6 ]. Other studies demonstrated a correlation between abdominal symptoms and an increase in inflammatory markers in the stool [ 7 , 8 ], undermining the hypothesis derived from CF animal models that inflammation, secondary to bacterial overgrowth, predisposes to obstructive episodes, disease severity, and abdominal complications [ 9 , 10 , 11 ]. However, this hypothesis has not been validated in animal models or CF patients.…”
Section: Introductionmentioning
confidence: 99%